2006
DOI: 10.1007/s10750-006-0372-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of critical prey items to Appalachian brook trout (Salvelinus fontinalis) with emphasis on terrestrial organisms

Abstract: Brook trout (Salvelinus fontinalis) in Appalachia experience prolonged periods of poor feeding conditions, particularly during summer and fall. To determine which prey organisms are important in sustaining brook trout populations, we monitored the feeding patterns of a population of brook trout over the course of 2 years with an emphasis on seasonal change. We employed a bioenergetics model to estimate whether or not each fish had obtained enough energy to meet daily metabolic demand. As a result, qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 35 publications
4
50
0
Order By: Relevance
“…For all months (except May 2004), no single scarabaeid species was ranked as the most important prey item, but the entire family ranked very high in both frequency of occurrence in brook trout stomachs and in mean energy provided per capture. As a family, guchi and Nakano 2001; Kawaguchi et al 2003), Alaskan (Wipfli 1997) and eastern United States streams (Forrester et al 1994;Utz and Hartman 2007;Sweka and Hartman, in press). However, few researchers have identified a specific family or species of terrestrial organism that provides a large amount of energy as consistently as do the scarabaeids in the Middle Fork River watershed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For all months (except May 2004), no single scarabaeid species was ranked as the most important prey item, but the entire family ranked very high in both frequency of occurrence in brook trout stomachs and in mean energy provided per capture. As a family, guchi and Nakano 2001; Kawaguchi et al 2003), Alaskan (Wipfli 1997) and eastern United States streams (Forrester et al 1994;Utz and Hartman 2007;Sweka and Hartman, in press). However, few researchers have identified a specific family or species of terrestrial organism that provides a large amount of energy as consistently as do the scarabaeids in the Middle Fork River watershed.…”
Section: Resultsmentioning
confidence: 99%
“…However, few researchers have identified a specific family or species of terrestrial organism that provides a large amount of energy as consistently as do the scarabaeids in the Middle Fork River watershed. When taxonomic detail has been applied to terrestrial organisms in salmonid diets, terrestrial beetles usually emerge as very important (Allan 1981;Wipfli 1997;Kawaguchi and Nakano 2001;Utz and Hartman 2007). In a nearby watershed, Sweka (2003: Appendix A) found that scarabaeids contributed as much as 63% of the total ingested prey weight for brook trout populations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, inputs of terrestrial invertebrates from riparian canopy cover may represent an important food resource for stream-dwelling fish species (Kawaguchi and Nakano, 2001;Utz and Hartman, 2007;Syrjänen et al, 2011). Therefore, the importance of terrestrial invertebrates in riverine systems is unquestionable, such importance has been identified in different ways; that is, in terms of energy subsidy for fish species (Edwards and Huryn, 1996;Nakano et al, 1999b;Utz and Hartman, 2007), annual fish production (Edwards and Huryn, 1995), food resource partitioning between sympatric fish species (Dineen et al, 2007; or ecosystem functioning (Nakano et al, 1999c). That said, it should be kept in mind that the terrestrial invertebrate input to the riverine systems greatly depends on riparian canopy cover (Edwards and Huryn, 1996;Kawaguchi and Nakano, 2001;Ryan and KellyQuinn, 2015), but this allochthonous prey supply occurs primarily during summer, when aquatic invertebrate biomass is usually low (Nakano and Murakami, 2001).…”
Section: Introductionmentioning
confidence: 99%